Diarrhoea among Children under Five Years Old in Relation to Household Safe Storage Practices in Wukari Local Government Area, Taraba State, Nigeria - Kenneth, Imarenezor Edobor Peter; Hassan, Boyi; Ngozi, Opara Christiana; Samson, Efere Yarwadum (Darul Yasin Al Sys, 2026)
Diarrhoea remains a leading cause of morbidity and mortality among under‑five children in Nigeria, particularly in rural settings where unsafe water handling and inadequate storage prevail. Diarrhea is defined as the passing of three or more watery or loose stools per day, or more frequent passage than normal for an individual. This cross‑sectional study assessed the determinants of diarrhoea in relation to household water practices in Wukari Local Government Area (LGA), Taraba State. The aim was to identify water‑related risk factors—source type, treatment method, storage container, and hygiene behaviours—that influence diarrhoeal occurrence among children <5 years. A community‑based survey was conducted across randomly selected areas of Wukari LGA. Structured questionnaires captured socio‑demographics, water source (protected well, borehole, surface, sachet), treatment (boiling, chlorination, filtration, none), storage (covered narrow‑necked jerry can, open bucket, other), and hand‑washing practices. A total number of 200 sample were collected for this study among children of five (5) years of age. The result shows a prevalence of 34% (n=200) representing 34% (68) respondents of positive and 66% representing 132 respondents of negative. In conclusion, this study demonstrates that despite relatively high access to improved water sources (protected wells/boreholes) in Wukari, the prevalence of diarrhoea among children under five remains elevated (34%) because of pervasive unsafe practices downstream—principally failure to treat water before consumption, storage in uncovered buckets that permit re‑contamination, and fetching water with unclean hands. Microbiological evidence confirmed significantly higher faecal coliform counts in open‑bucket water, substantiating the causal pathway. Maternal education acted as a buffer, underscoring the role of health literacy. The findings indicate that interventions must shift focus from mere source improvement to promoting point‑of‑use safety—treatment, covered storage, and hand hygiene—to achieve meaningful reductions in diarrhoeal disease. To this end, it is recommended that; Community‑based water safety education, provision of affordable safe‑storage vessels, point‑of‑use water treatment promotion, strengthen maternal health literacy, microbial monitoring, policy advocacy and research follow‑up. Implementation and follow‑up practices which has to do with giving priorities to areas with highest diarrhoea prevalence (identified in survey) for rapid rollout; monitor via existing Integrated Disease Surveillance & Response (IDSR) system will reduce the prevalent rate of under-five diarrrhoea in Wukari which by extension Taraba State and North East in general.